2007
DOI: 10.1021/jp0743572
|View full text |Cite
|
Sign up to set email alerts
|

The Sulfur Dioxide−1-Butyl-3-Methylimidazolium Bromide Interaction:  Drastic Changes in Structural and Physical Properties

Abstract: The contact between minor amounts of SO2 and crystalline 1-butyl-3-methyl-imidazolium bromide (BMIBr) causes the almost immediate melting of the ionic liquid (mp 45 degrees C) as well as a dramatic decrease in its viscosity in comparison to the pure molten phase. The same behavior was observed for other halide ionic liquids of higher melting points (70, 135, and 220 degrees C). The Raman spectrum of BMIBr-SO2 clearly indicates a specific charge transfer interaction involving SO2 and the halide. The measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
129
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(145 citation statements)
references
References 11 publications
15
129
0
1
Order By: Relevance
“…[21] Vertical absorption electronic spectra were computed at the B3LYP/6-311++G(3df,3pd) optimized geometries employing TDDFT protocol implemented in Gaussian03 package, following similar procedure successfully employed previously. [22] Bond length (Å) 3 1.3873 1.3857 C 3 -C 4 1.3896 1.3911 C 4 -C 5 1.3896 1.3867 C 5 -C 6 1.3873 1.3909 C 6 -C 1 1.4088 1.3984 C 1 -N 9 1.3882 1.4237 N 9 -C 7 1.4503 1.4593 N 9 -C 8 1.4503 1.4669 N 9 -S 10 2.6009 S 10 -O 11 1.4461 a S 10 -O 12 1.4483 a a S-O bond distance calculated for free SO 2 = 1.4367. Figure 1 shows schematically the DMA molecule and the calculated optimized geometry for the complex DMA-SO 2 with the respective atom numbering.…”
Section: Calculation Detailsmentioning
confidence: 99%
“…[21] Vertical absorption electronic spectra were computed at the B3LYP/6-311++G(3df,3pd) optimized geometries employing TDDFT protocol implemented in Gaussian03 package, following similar procedure successfully employed previously. [22] Bond length (Å) 3 1.3873 1.3857 C 3 -C 4 1.3896 1.3911 C 4 -C 5 1.3896 1.3867 C 5 -C 6 1.3873 1.3909 C 6 -C 1 1.4088 1.3984 C 1 -N 9 1.3882 1.4237 N 9 -C 7 1.4503 1.4593 N 9 -C 8 1.4503 1.4669 N 9 -S 10 2.6009 S 10 -O 11 1.4461 a S 10 -O 12 1.4483 a a S-O bond distance calculated for free SO 2 = 1.4367. Figure 1 shows schematically the DMA molecule and the calculated optimized geometry for the complex DMA-SO 2 with the respective atom numbering.…”
Section: Calculation Detailsmentioning
confidence: 99%
“…In 2007, Santos et al 32 firstly reported an interesting phenomenon that the imidazolium salt [Bmim]Br experienced significant variations on the structures and physical properties such as density, viscosity and conductivity upon contact with gaseous SO 2 . It was worth mentioning that the density of [Bmim]Br increased slightly and the viscosity decreased dramatically in the presence of SO 2 , which provides the possibility by using SO 2 gas to modulate the physical properties of ILs.…”
Section: Introductionmentioning
confidence: 99%
“…For example, multiple sterically hindered allylic functional groups could be incorporated to minimize IL-electrode interactions and maximize compressibility of the solvation layers [22][23][24]. It was reported that the adsorption and dissolution of gas molecules in the IL-electrified metal interface can lead to the change of the doublelayer structure and thickness and the change of IL viscosity and the dielectric constant (i.e., less organized arrangement of ILs) [25,26]. The molecular structure of ILs such as alkyl chain length influences the relative permittivity [27].…”
Section: Electrical Double Layermentioning
confidence: 99%